Atelier Notebook Intertwinings Between Art and Life (Revista Apotheke, 2026)
This article chronicles a research trajectory that approaches the teacher’s planning notebook as a device for artistic creation and pedagogical authorship. Evolving from its original function of organization, the object transforms into a territory for aesthetic experimentation and critical reflection, where pedagogical planning and artistic investigation organically coexist, the Atelier Notebook. The theoretical framework articulates Madalena Freire’s (1983) concept of planning, Ana Mae Barbosa’s (1991) Triangular Approach (with its pillars of knowing, reflecting, and producing), and John Dewey’s (2010) philosophy of art as experience, which conceives everyday life as the raw material for both artistic and educational practice. The discussion advances in dialogue with Conceição Evaristo’s concept of “escrevivência” (writing-living) and the curatorial work of Koyo Kouoh, both of whom value narratives in “minor keys” and the aesthetic power of the ordinary. The analysis of this journey, documented over two decades, demonstrates how the Atelier Notebook becomes a living archive of the teaching-learning process, a laboratory for graphic and chromatic studies, and ultimately, the premise for artworks that overflow its pages, such as murals and paintings. It is concluded that this practice legitimizes the educator as a cultural producer and reveals how the extraordinary can inhabit the ordinary, inviting a re-evaluation of one’s own daily records as acts of poetic insurgency and authorship.
Keywords: notebook; authorship; experience; daily life; creation